Sammenhæng i læreruddannelse: Hvad, hvorfor, og i erkendelsen af kompleksitet? - Lund, Jens H.; Nielsen, Birgitte Lund (Tidsskrift for Professionsstudier, 2019)
The article departs from the observation, that without further definition the concept coherence is very frequently used in didactical and teacher educational discussions and furthermore used with very positive connotations. Based on theoretical and empirical analyses the article describes categorically different meanings of the concept. One conclusion is that considerable differences occur in the way the concept is used in the documents compared to the way it is used and ascribed meaning by the educators in teacher education. The article recommends to promote discussions about the student teachers’ perceptions of coherence in ways that address the complexity of both teacher education and teaching in schools.